2009
DOI: 10.1038/oby.2008.664
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Overall Obesity and Body Fat Distribution in Predicting Risk of Mortality

Abstract: Results of studies comparing overall obesity and abdominal adiposity or body fat distribution with risk of mortality have varied considerably. We compared the relative importance and joint association of overall obesity and body fat distribution in predicting risk of mortality. Participants included 5,799 men and 6,429 women aged 30–102 years enrolled in the third National Health and Nutrition Examination Survey who completed a baseline health examination during 1988–1994. During a 12‐year follow‐up (102,172 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
133
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 37 publications
6
133
1
1
Order By: Relevance
“…These findings suggest that defining obesity on the base of WC, HC, or WHR may be equally valid and useful methods for use in epidemiological research and clinical practice. Our results are in agreement with another study identified a high correlation between WC and BMI and suggested this could imply that WC is not only an indicator of abdominal adiposity but also overall obesity (Reis et al 2009). However, other studies have suggested that WHR to be a better predicator of CVD risk (Bigaard et al 2004).…”
Section: Discussionsupporting
confidence: 83%
“…These findings suggest that defining obesity on the base of WC, HC, or WHR may be equally valid and useful methods for use in epidemiological research and clinical practice. Our results are in agreement with another study identified a high correlation between WC and BMI and suggested this could imply that WC is not only an indicator of abdominal adiposity but also overall obesity (Reis et al 2009). However, other studies have suggested that WHR to be a better predicator of CVD risk (Bigaard et al 2004).…”
Section: Discussionsupporting
confidence: 83%
“…Higher body mass index (BMI) in older people is associated with higher survival rates, in contrast to middle-aged people (Adams et al 2006;Al Snih et al 2007;Reis et al 2009;Auyeung et al 2010;Janssen 2007;Tamakoshi et al 2010). This has led to the postulation that obesity might be less harmful or even protective in old age (Al Snih et al 2007;Reis et al 2009;Auyeung et al 2010;Lea et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the postulation that obesity might be less harmful or even protective in old age (Al Snih et al 2007;Reis et al 2009;Auyeung et al 2010;Lea et al 2009). Yet, BMI is a measure of overall adiposity, which makes no distinction between fat elsewhere and abdominal fat, the latter being metabolically more harmful (Lapidus et al 1994;Chang et al 2000;Snijder et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Increased abdominal adiposity is associated with adverse cardiovascular outcomes (Berg and Scherer 2005) and was also repeatedly related to impaired lung function (Leone et al 2009;OchsBalcom et al 2006;Wehrmeister et al 2012). In studies relying on waist-to-hip ratio, waist circumference, or imaging techniques as markers of intra-abdominal fat tissue, higher abdominal fat mass was most often associated with increased overall mortality (Bigaard et al 2005;Reis et al 2009;Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 99%